Reconsidering "We can do it!" : Rosie the Riveter and U.S. women’s labor relations - Smith, Michelle C., (SAGE Business cases., 2024)
In the 1940s United States, government and industry collaborated to supply the materials needed for success in World War II. These collaborations involved complex information campaigns overseen by government agencies like the War Manpower Commission, the Office of War Information, and the War Production Board to promote certain objectives and aims of the war effort and encourage collaboration between government, industry, and the public. Posters circulated in workplaces as well as public spaces like post offices and libraries sold the ideology of the "home front," redefining the factory and the home as areas of war. Perhaps the most famous image from this propaganda onslaught is the "We Can Do It!" poster now commonly known as Rosie the Riveter. Over time, this poster has been decontextualized from its wartime origins and reinterpreted as a feminist icon. Resituating the poster in its original context and exploring its reinterpretation and redeployment illuminates government–industry collaborations during WWII and raises enduring challenges for diversity in the workforce.